Financial Technology and Green Financing: A Blend of Technology, Economy, and Environment - Hengky Kosasih; Poppy Wulandari (Indonesian Journal of Social Economics and Agricultural Policy (IJSEAP), 2025)
This study examines the integration of financial technology (fintech) and green financing in supporting sustainable development. Although fintech has shown great potential in accelerating access to financing for environmentally friendly projects, there is a gap in understanding how the three elements—technology, economy, and environment—can collaborate effectively to achieve maximum impact on sustainability. This research aims to explore how the blend of financial technology and green financing can produce more efficient and sustainable financing models. Using a qualitative approach and literature review, this study analyzes the integration of these three aspects and their impact on sustainable development. The findings suggest that the collaboration between technology and green financing can create efficient funding flows, enhance transparency, and promote inclusive economic growth and carbon emission reduction, directly supporting the achievement of global sustainability goals.